THE ALLURE OF THE TRANSNATIONAL: Notes on Some Aspects of the Political Economy of Water in India - Ananthakrishnan Aiyer
Over the past decade, environmental and social justice activists have increasingly focused their attentions and energies on the privatization of water resources around the globe. Many of the debates and oppositional struggles surrounding this issue have focused on what has been termed the "corporate theft" of water resources. Opposition to transnational corporations like Suez, Vivendi, The Coca-Cola Company, among others, has focused on a range of issues from privatization and price gouging to bottling groundwater and environmental contamination. In this article, I focus on one small struggle forwater rights in Plachimada, Kerala, India. I use the Plachimada example to argue that corporate control of resources in India must be located and analyzed within a framework that is not restricted to neoliberal globalization and transnational Corporations. I suggest that the struggle of communities like Plachimada should be analyzed as part of the unfolding agrarian crisis in India. Corporate and government strategies to privatize water, along with other goods and services, have especially had a devastating effect on peasants and farmers in rural India and provide new avenues for the reconfigurations of intra- and interclass conflicts between and across the ural urban divide in neoliberal India. As academics and activists, we face the important task of combining "old" and "new" conceptual or theoretical and political concerns as we confront the exigencies and emergencies wrought by neoliberal globalization